DETERMINATION OF THE LEVEL OF VITAMIN D AND WHITE BLOOD CELL COUNT IN PATIENTS WITH ECZEMA - Huda Mohammad Kadhim Al-asady; Azal A. Al-Rubaeaee (Scholar Express Journals, 2023)
The cases of eczema have increased in recent times in societies and to study it, 40 blood samples were collected, distributed between 20 blood samples for people suffering from eczema and 20 blood samples from healthy people for comparison the results. In addition to recording information from eczema patients such as age and gender, and after diagnosis by the specialist doctor in the hospital ,the samples were collected and the results were recorded to study of the influence of level the vitamin-D in patients, also the difference of the white blood cells number in patients compared to healthy people. This period is from 20/12/2019 to 1/3/2020 in Al-Zobair Hospital in Basra/Iraq. The ages of the patients ranged between 1-65 years. The study included about 11 samples, 55% for men, and 9 samples for women, 45%. The results showed that there was a non- significant decreasing (P > 0.05) in concentration the vitamin D on patients with eczema, where it reached 12.15 ng / mL compared to healthy adults 25.5 ng / mL. And it was noted that the white blood cell numbers increasing significant (P < 0.05) which about 7.86× / 9 10 L was recorded in patients compared to 6.25× /9 10 L in healthy people.
Keywords: Eczema; Atopic dermatitis; Vitamin D; White Blood Cell